PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN GAME EDUKASI BERBASIS KAHOOT TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN PPKN DI KELAS X PERHOTELAN SMK NEGERI 6 KOTA JAMBI - Sari, Novita; Irwan, Irwan; Candra, Alif Aditya (Academy of Education Journal, 2023)
This study aims to determine the effect of using Kahoot-based educational game learning media on students' critical thinking skills in Civics Subjects in Class X Hospitality SMK Negeri 6 Jambi City. This research is motivated by educational problems, especially in technology and one of the low critical thinking skills of students with a proportion of 33%. The research method used the Pre-Experimental design with the One Group Pretest Posttest design. This research was conducted at SMK Negeri 6 Jambi City for the 2022/2023 academic year. The population in this study were all class X students of the Department of Hospitality SMK Negeri 6 Jambi City. The sampling technique in this study was purposive sampling. Retrieval of research data using a test. The data in this study were obtained from the pretest and posttest of the experimental class. The data was tested by t test using SPSS 22 Software. The results showed that there was an effect of the use of Kahoot-Based Game Learning Media on students' critical thinking skills in Civics Subjects in Class X Hospitality SMK Negeri 6 Jambi City. Judging from the results of data analysis, it was obtained that the average posttest score was 69.6% while the average pretest score was 36%. After testing the hypothesis using the Sample t Test, the characteristics are -10.213> 2.045, so there is an increase in the average pretest and posttest scores. As well as on the test, the sign value (2-tailed) on critical thinking skills is 0.000 <0.05, then Ho is rejected and Ha is accepted. So it can be concluded that there is an effect of using Kahoot-based educational game learning media on students' critical thinking skills.